TCR signaling and cellular metabolism regulate the capacity of murine epidermal γδ T cells to rapidly produce IL-13 but not IFN-γ - Ibusuki, Atsuko; Kawai, Kazuhiro; Nitahara-Takeuchi, Ayano; Argüello, Rafael J.; Kanekura, Takuro (Frontiers in Immunology, 2024)
Resident epidermal T cells of murine skin, called dendritic epidermal T cells (DETCs), express an invariant γδ TCR that recognizes an unidentified self-ligand expressed on epidermal keratinocytes. Although their fetal thymic precursors are preprogrammed to produce IFN-γ, DETCs in the adult epidermis rapidly produce IL-13 but not IFN-γ early after activation. Here, we show that preprogrammed IFN-γ-producing DETC precursors differentiate into rapid IL-13 producers in the perinatal epidermis. The addition of various inhibitors of signaling pathways downstream of TCR to the in vitro differentiation model of neonatal DETCs revealed that TCR signaling through the p38 MAPK pathway is essential for the functional differentiation of neonatal DETCs. Constitutive TCR signaling at steady state is also needed for the maintenance of the rapid IL-13-producing capacity of adult DETCs because in vivo treatment with the p38 MAPK inhibitor decreased adult DETCs with the rapid IL-13-producing capacity. Adult DETCs under steady-state conditions had lower glycolytic capacity than proliferating neonatal DETCs. TCR stimulation of adult DETCs induced high glycolytic capacity and IFN-γ production during the late phase of activation. Inhibition of glycolysis decreased IFN-γ but not IL-13 production by adult DETCs during the late phase of activation. These results demonstrate that TCR signaling promotes the differentiation of IL-13-producing DETCs in the perinatal epidermis and is needed for maintaining the rapid IL-13-producing capacity of adult DETCs. The low glycolytic capacity of adult DETCs at steady state also regulates the rapid IL-13 response and delayed IFN-γ production after activation.